Impact Of Duck Rearing Training On Technology Dissemination And Income Of Women Under Microfinance And Technical Support (Mfts) Programme Of Selected Area Of Bangladesh - Alam, R; Akteruzzaman, M; Hossain, MM; Sharmin, E (Bangladesh Journal of Animal Science, 2012)
A total of 80 duck farms were randomly chosen from three selected districts for survey during the period of January to March 2006. Evidence shows that most of the respondents (93%) received training from Micro-Finance and Technical Support (MFTS) partner organization in Kishoregonj, Brahmanbaria and Habigonj district. It is evident that the respondents adopted duck rearing farming technology about 60-80% which varie from area to area. The dissemination of duck rearing took place in the MFTS project areas due to interventions of MFTSP through training followed by production credit. The duck farming was found profitable and on an average Tk. 3318 earned which was about 14% of the net change of income due to duck rearing technology in the MFTS project areas. This improved the socio-economic and livelihood status. Finally a set of recommendations were made for making MFTS project activities more effective. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9870 BJAS 2008; 37(1): 63-69